The Campus Canopy, 1940-02-16 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, February 16, 1940. Vol. 6, No. 14. -- Morgan Says Singing Ability Was Discovered By Imitating Her Aunt -- Smith, Burns To Lead Out At Freshman-Junior Formal -- Carpenter Compares Girls Of ’13 And ’40 -- English Club Has Panel Discussion -- GSWC - Emory Junior To Sponsor Noted Speakers -- Social Calendar
Digitized from original print, Valdosta State University Archives and Special Collections, December 9, 2016.
Keywords: The Campus Canopy; 1940s; 1940; The Georgia State Woman's College; GSWC; Valdosta State College; VSC; Valdosta State University; VSU